ANZCA 2021 President's welcoming address. Issue 2 (3rd April 2022) - Park, Sora
ABSTRACT: This article is based on the President's Welcoming Address delivered on Wednesday 7 July 2021 at the 26th Annual Conference of the Australian and New Zealand Communication Association, which was held virtually during the COVID-19 pandemic.